Green Synthesis of Silver Nanoparticles Using Extract of Oak Fruit Hull (Jaft): Synthesis and In Vitro Cytotoxic Effect on MCF-7 Cells - Rouhollah Heydari; Marzieh Rashidipour (International Journal of Breast Cancer)
A green synthetic approach by using oak fruit hull (Jaft) extract for preparation of silver nanoparticles (AgNPs) was developed and optimized. Parameters affecting the synthesis of AgNPs, such as temperature, extract pH, and concentration of extract (ratio of plant sample to extraction solvent), were investigated and optimized. Optimum conditions for the synthesis of silver nanoparticles are as follows: Ag+ concentration, 1 mM; extract concentration, 40 g/L (4% w/v); pH = 9 and temperature, 45°C. Biosynthesized silver nanoparticles were characterized using UV-visible absorption spectroscopy (UV-Vis), Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), dynamic light scattering (DLS), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). TEM and DLS analyses have shown the synthesized AgNPs were predominantly spherical in shape with an average size of 40 nm. The cytotoxic activity of the synthesized AgNPs and Jaft extract containing AgNPs against human breast cancer cell (MCF-7) was investigated and the half maximal inhibitory concentrations (IC50) were found to be 50 and 0.04 μg/mL at 24 h incubation, respectively. This eco-friendly and cost-effective synthesis method can be potentially used for large-scale production of silver nanoparticles.